Cytokine Storm score (CSs) in COVID-19 Patients Smokers at Dr. Saiful Anwar Malang - Resti Fitriani Yuliawati; Tri Wahju Astuti; Yani Jane Sugiri (RSUP Dr. Kariadi, 2023)
Background: After 3 years of the COVID-19 pandemic, its escalation is still causing a critical global health problem. Cytokine storm is a severe complication of COVID-19, and smoking is a risk factor for death. The prevalence of smoking in Indonesia is very high, but there is still little research on the effect of smoking on the occurrence of cytokine storms. The Cytokines Storm Score (CSs) is a quick and simple method for detecting cytokine storms early by utilizing D-dimer, lactate dehydrogenase (LDH), ferritin, and C-reactive protein (CRP) parameters. Objective: To evaluate CSs in COVID-19 patients smokers Methods: Retrospective analysis of 120 confirmed COVID-19 patients in November 2020–2021, divided into 2 groups (60 smokers and nonsmokers), male, without comorbidities. analysis using Chi-square and Mann-Whitney. Prior to the CSs examination, lymphopenia is required. CSs were positive if at least two of the D-dimer, LDH, or ferritin levels were elevated. The CRP level is measured if there is an increase in only one of these values. Elevated CRP, lymphopenia, and impaired D-Dimer, LDH, or ferritin will result in positive CSs. Results: CSs were significantly higher in smokers than non-smokers (54.5% vs. 45.5%, p = 0.024). D-dimer and CRP levels were significantly higher in smokers than non-smokers (1620 ng/mL vs. 1002.5 ng/mL, p = 0.001; and 13.8 mg/dL vs. 7.75 mg/dL, p = 0.001). Lower LDH and higher ferritin levels were not significant in smokers compared to nonsmokers (405.5 IU/L vs. 418 IU/L, p = 0.160; and 886.65 ng/mL vs. 790.5 ng/mL, p = 0.203). Conclusion: Cytokines Storm scores (CSs) increased significantly in COVID-19 patients who smoked, D-dimer and CRP levels were significantly higher in smoking COVID-19 patients compared to non-smokers